Cross-border acquisitions by state-owned and private enterprises: A perspective from emerging economies - Reddy, K.S. (369 EGFR SIGNALING IMPAIRS THE ANTIVIRAL ACTIVITY OF INTERFERON-ALPHA, 2016)
Leveraging insights from the institutional theory, resource- and industry-based views and OLI paradigm, we conceptually design a dialectic globalization framework to analyze the acquisition strategy of emerging economy (EE) enterprises. Firstly, we provide trend analysis of the market for cross-border acquisitions by Chinese and Indian multinationals over the last two decades, 1995–2014. Specially, this paper, to date, is the first to analyze high-valuation cross-border acquisitions of Chinese state-owned (SOEs) and Indian private enterprises (POEs). Based on 61 high-valuation deals valued at approximately US$200 billion, we find that Chinese SOEs completed more high-valuation deals, seek to invest in resource-scarce industries, and diversify their risk by targeting developed, emerging and developing countries. While Indian POEs largely prefer to invest in developed economies for both market and strategic-asset seeking, and follow an effective portfolio matrix by concentrating diversified sectors. Lastly, we discuss several policy implications pertaining to disinvestment and turnaround strategy of loss-making SOEs in EE, national interest and security concerns over EE state-driven outbound acquisitions, and foreign investment regulations.